Fiqh muamalah overview of electronic money products at linkAJA shariah - Alif Farhan Cahairul; Roni Hidayat; Iqbal Fadli Muhammad (Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research reveals a fiqh muamalah review of electronic money on LinkAja Syariah and analyzes journals, classic books, DSN-MUI fatwas as well as related regulations. The research method used is a qualitative descriptive method with secondary data sources obtained from previous research by linking it with the MUI DSN Fatwa, AAOIFI Standards, and classical books. This research is literature research (library research). The data collection technique used was literature study and documentation. The results of this study are that the practice of electronic money in LinkAja Syariah has met the principles of sharia in implementing the electronic money scheme on products that have been analyzed by researchers and from the point of view of maqashid sharia, electronic money schemes give birth to many maslahat